What Drives Aggregate Investment? - Ruediger Bachmann; Peter Zorn (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using firm-level survey data for the West German manufacturing sector, this paper revisits the technology-driven business cycle hypothesis for the case of aggregate investment. We construct a survey-based measure of technology shocks to gauge their contribution to short-run investment fluctuations. We estimate an upper bound for the contribution of technology shocks to the variance of the aggregate investment growth rate of 19 percent. The larger part of fluctuations in aggregate investment can be attributed to finance and demand shocks, which we also extract from the survey data.
Keywords: E20; E22; E30; E32; O47; 330; technology shocks; investment dynamics; investment determinants; survey data